Respuesta :
[tex]\bold{Answer}[/tex]
[tex]\boxed{\bold{\left(2u-7\right)^2}}[/tex]
[tex]\bold{Explanation}[/tex]
- [tex]\bold{Factor: \ 4u^2-28u+49}[/tex]
[tex]\bold{---------------------}[/tex]
- [tex]\bold{Rewrite \ 4u^2-28u+49: \ \left(2u\right)^2-2\cdot \:2u\cdot \:7+7^2}[/tex]
[tex]\bold{\left(2u\right)^2-2\cdot \:2u\cdot \:7+7^2}[/tex]
- [tex]\bold{Apply \ Perfect \ Square \ Formula \ \left(a-b\right)^2=a^2-2ab+b^2: \ a=2u,\:b=7}[/tex]
[tex]\bold{\left(2u-7\right)^2}[/tex]
[tex]\boxed{\bold{Eclipsed}}[/tex]
Answer:
(2u - 7)^2
Step-by-step explanation:
4u^2-28u+49
= (2u)^2 - 2*(2u)*(7) + 7^2
= (2u - 7)^2